ADAB PEMBELAJARAN AL-QURAN: STUDI KITAB AT-TIBYAN FI ADABI HAMALATIL QURAN - Ismail Ismail; Abdulloh Hamid (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
This research is an attempt to know the courtesy reading the Quran in the book of At-Tibyan fi Adabi Hamalatil Quran by Imam Nawawi. The question that is to be answered through this study is (1) how the courtesy to read Al-Quran in the book At-Tibyan, (2) How does the relevance of courtesy to read the Qur'an in the book of At-Tibyan in contemporary times? The research methods use library research. This study is conducted using data collection techniques by conducting observations on certain sources, seeking, studying books, articles, journals, theses or others related to this study. Data collection is divided into two sources, namely primary and secondary data. Then the data are analyzed using descriptive and contextual methods. The results show that courtesy reading the Quran in the book of At-Tibyan fi Adabi Hamalatil Quran includes: Solemn, sincere, ethical, clean and holy State, facing the Qibla, start with Ta'awudz. While the relevance of courtesy reading the Quran in the book of At-Tibyan fi Adabi Hamalatil Quran with the context of contemporary can be a solution in improving the manners of interacting with the Quran, especially in the face of today's characteristics or contemporary.